Impact of Chemical Composition of Fire Foams on the Environment and Human Health - Gurbanova, M.A.; Hajızade, F.M. (Herald of Azerbaijan Engineering Academy, 2021)
Per and polyfluoroalkyl substances (PFAS, also perfluorinated alkylated substances) are considered pollutants in the environment because they are present in the environment, biota and humans. The article discusses the toxic effect of fire foam components and the degree of damage to the environment. In this regard, PFAS compounds were found in their blood in various concentrations. Data on the toxicity of these compounds have been obtained almost exclusively from environmental studies, but data on their adverse effects on human health have been limited to a small number of professional studies. Although there is limited research on the effects of PFAS on humans, there are serious health problems associated with the widespread use of these compounds in the human population, especially given their very persistent and biocollective nature and potential developmental effects.